2013
DOI: 10.1158/0008-5472.can-13-0324
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm for Simplification of Complex Gene Classifiers in Cancer

Abstract: The clinical application of complex molecular classifiers as diagnostic or prognostic tools has been limited by the time and cost needed to apply them to patients. Using an existing fifty-gene expression signature known to separate two molecular subtypes of the pediatric cancer rhabdomyosarcoma, we show that an exhaustive iterative search algorithm can distill this complex classifier down to two or three features with equal discrimination. We validated the two-gene signatures using three separate and distinct … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There has been abundant research to evaluate whether gene expression profiling can be used to risk-stratify cancer patients at diagnosis. First demonstrated to be feasible in breast cancer [7], this prognostic approach has been evaluated and validated in other human cancers [8,9], including paediatric malignancies such as neuroblastoma [10][11][12], rhabdomyosarcoma [13][14][15], and leukaemia [16,17]. Several small ES genome-wide profiling studies have been reported, and non-overlapping candidate prognostic biomarkers were identified [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…There has been abundant research to evaluate whether gene expression profiling can be used to risk-stratify cancer patients at diagnosis. First demonstrated to be feasible in breast cancer [7], this prognostic approach has been evaluated and validated in other human cancers [8,9], including paediatric malignancies such as neuroblastoma [10][11][12], rhabdomyosarcoma [13][14][15], and leukaemia [16,17]. Several small ES genome-wide profiling studies have been reported, and non-overlapping candidate prognostic biomarkers were identified [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the nCounter assay allows for RNA extracted from FFPE tissues to be analyzed for gene expression. This approach shows excellent correlation with Taqman based RT-PCR approach (19), and RNA expression quantified by nCounter has been used to discriminate FN from FP RMS (20). The nCounter assay has also been used and validated in other tumor types such as breast cancer and neuroblastoma (21, 22).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of genomewide mRNA expression reveals that RMSp and RMSn show distinct expression profiles, and that ERMS is indistinguishable from ARMSn within the larger RMSn group [16, 23, 24]. Further, mRNA expression profiles can identify distinct outcome groups within RMSp or within each COG risk strata [23, 25], as well as predicting PAX-FOXO1 fusion status [26]. Studies of RMSn identified an mRNA expression signature derived from the weighted expression of five genes ( EPHA2, EED , NELF, CBS and EPB41L4B ) that can distinguish patient outcomes [19].…”
Section: Mrna Expression Signatures Correlate With Outcomes For Rmsnmentioning
confidence: 99%